Amniotic Fluid. Hormones. - Ludmir Grimberg, Abraham (2015)
The hormones found in amniotic fluid are the type of protein and steroid hormones, and their presence in such behavior could give an accurate picture of the placenta and fetal status, if it was known or could be made integral equations to express the concentration precise in a given substances in different compartments time.